Scarcity Cues, Payment Convenience, and FOMO: Their Roles in Online Impulsive Buying and Post-Purchase Cognitive Dissonance - Abero, Zaira Marie; Babanto, Grezyle May; Pagara, Jethryl; Abellana, Jupert Jasser (International Review of Management and Marketing, 2026)
This study investigates the influence of time-limited discounts, use of e-wallet payments, and fear of missing out (FOMO) on online impulsive buying and subsequent post-purchase cognitive dissonance among public university students. A total of 400 respondents from Mindanao State University-Iligan Institute of Technology, predominantly aged 18–19 (50.0%) and primarily female (73.7%), participated in the research. Data were collected through a structured questionnaire utilizing a 5-point Likert scale and analyzed using t-tests, one-way ANOVA, and Pearson Product-Moment Correlation. Findings indicate that participants reported above-average agreement with time-limited discounts (Mean = 3.61) and the use of e-wallet payments (Mean = 3.60), alongside elevated levels of post-purchase cognitive dissonance (Mean = 3.56). In contrast, online impulsive buying (Mean = 2.79) and FOMO (Mean = 2.32) were reported at moderate to low levels. Significant sex-based differences were observed, with male students demonstrating higher responsiveness to promotional urgency (Mean = 3.66) and use of e-wallet payments than female students. Age-related analysis revealed that older students reported significantly higher use of e-wallet payments, while younger students experienced slightly higher levels of post-purchase dissonance. Correlation results showed that time-limited discounts and FOMO were positively and significantly associated with both online impulsive buying and post-purchase dissonance. Use of e-wallet payments was positively related to online impulsive buying but not to post-purchase cognitive dissonance. Online impulsive buying demonstrated a strong positive relationship with post-purchase cognitive dissonance. These findings illuminate the psychological and contextual dynamics of digital impulse buying in an emerging Southeast Asian market.